2012
DOI: 10.1007/s00264-012-1630-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical repair of hip abductors. A new technique using Graft Jacket® allograft acellular human dermal matrix

Abstract: Purpose Avulsion of the abductors from the hip can be an infrequent but debilitating complication after total hip arthroplasty performed through a trans-gluteal approach. This can result in intractable pain, limp, Trendelenberg lurch and instability of the hip. There have been various methods described for repairing or reconstruction of this abductor muscle complex including direct trans-osseous repair, muscle transfers, muscle and tendon sling, bone tendon allograft reconstruction and endoscopic repair techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 22 publications
3
55
0
Order By: Relevance
“…Open techniques have evolved to suture anchors and even more complex models, such as the Ligament Augment and Reconstruction System (LARS, Arc sur Tille, France) 19,20 and biologic patch augmentation. [21][22][23] Voos et al 7,24 described the first endoscopic technique using suture anchors in 2007 and reported no pain or complications in all 10 patients at a mean follow-up of 25 months. More recent reports have confirmed excellent patient-reported outcomes at similar time points after endoscopic repair.…”
Section: Discussionmentioning
confidence: 99%
“…Open techniques have evolved to suture anchors and even more complex models, such as the Ligament Augment and Reconstruction System (LARS, Arc sur Tille, France) 19,20 and biologic patch augmentation. [21][22][23] Voos et al 7,24 described the first endoscopic technique using suture anchors in 2007 and reported no pain or complications in all 10 patients at a mean follow-up of 25 months. More recent reports have confirmed excellent patient-reported outcomes at similar time points after endoscopic repair.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have a strong clinical implication. Acellular matrices have evolved becoming suitable scaffolds for soft tissue reconstruction [1,2,[5][6][7] due to their reduced antigenicity caused by the partial or complete absence of cellular proteins [9]. We could show previously that acellularisation-related effects are tissuedependent [8].…”
Section: Discussionmentioning
confidence: 99%
“…Being freed of cells and cellular components, these scaffolds produce minute antigenicity [2,6,9] and provide a biologic environment for cellular ingrowth and subsequent remodelling. However, there is a lack of morphologic and functional data on how exactly the commonly used methods of acellularisation impact extracellular matrix integrity, including commonly used chemical and physical protocols [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…The anterolateral THA approach is associated with potential complications including superior gluteal nerve injury or failure of the abductor muscle repair [30]. GTPS can present as an early or late finding.…”
Section: Risk Factors and Associated Conditionsmentioning
confidence: 98%
“…Active and passive abduction of the post-operative hip is avoided for the initial 6 weeks. Subsequently, patients are allowed to perform passive hip abduction for activities of daily and progress to active hip abduction strengthening exercises under physical therapy instruction [30].…”
Section: Surgerymentioning
confidence: 99%